Early Trauma and Cognitive Functions of Patients With Schizophrenia - Carrilho, Carolina G.; Cougo, Simone S.; Bombassaro, Tatiane; Varella, André Augusto B.; Alves, Gilberto S.; Machado, Sergio; Murillo-Rodriguez, Eric; Malaspina, Dolores; Nardi, Antonio E.; Veras, André B. (Frontiers in Psychiatry, 2019)
Aim: The following work aims to investigate the putative correlation between early trauma and cognitive functions, as well as psychotic symptoms and cognitive functions, in individuals diagnosed with schizophrenia. Methods: A quantitative assessment was performed with 20 individuals diagnosed with schizophrenia according to the 5th edition of the Diagnostic and Statistical Manual (DSM-5) criteria and who were in ongoing outpatient treatment in Psychosocial Care Centres in Brazil. Clinical measurements comprised a semistructured clinical interview, a screening questionnaire for common mental disorders, the Positive and Negative Syndrome Scale (PANSS), and the Early Trauma Inventory Self-Report—Short Form (ETISR-SF). Cognitive assessment included Beta III test, Concentrated Attention (CA) test, Color Trails Test (CTT), and Visual Face Memory (VFM) test. Results: Age-adjusted analysis showed a negative correlation between early trauma and visual memory performance (r = −0.585, p = 0.007) and negative symptoms and attention performance (r = −0.715, p = 0.000). Conclusion: Although a cause–effect relationship cannot be firmly stated, an association between early trauma experience and cognitive impairment such as visual memory, as well as a relationship between negative symptoms and attention domains, is suggested by our preliminary findings. Future studies with larger sample sizes and prospective design will clarify the long-term effects of early exposure to trauma and its clinical meaning in terms of developing psychotic-related illness.